Transformation obsessions in paediatric obsessive-compulsive disorder: Clinical characteristics and treatment response to cognitive behaviour therapy. (September 2015) - Monzani, B.; Jassi, A.; Heyman, I.; Turner, C.; Volz, C.; Krebs, G.
Abstract: Background and objectives: Transformation obsessions denote an under-reported symptom of Obsessive Compulsive Disorder (OCD), characterised by an excessive fear of turning into another person/object or acquiring unwanted characteristics. Relative to other OCD symptoms, little is known about the clinical presentation of transformation obsessions. The study aims to examine the clinical correlates and treatment prognosis of transformation obsessions in a paediatric OCD sample. Methods: The sample consisted of 346 youths with a primary diagnosis of OCD. Patients with and without transformation obsessions were compared in terms of demographic and clinical characteristics, and CBT outcomes. Results: 10% of the sample endorsed transformation obsessions. Patients with transformation obsessions were more likely to be boys, to be on augmented medication regimes, and to present with more severe obsessions at assessment. A factor analysis identified four major OCD symptom clusters, with transformation obsessions loading on a 'forbidden thoughts' factor alongside aggressive, sexual, and religious obsessions. No group differences in treatment outcomes were observed. Limitations: Limitations include the cross-sectional and retrospective nature of the study, the representativeness of our sample, and use of concomitant medication, among others. Conclusions: The study provides the first empirical evidence regarding phenomenological similarities and differences between paediatric OCD patients presenting with and without transformation obsessions. The findings suggest that transformation obsessions are best conceptualised as related to 'forbidden' obsessions and respond to exposure-based CBT. Highlights: Little is known about 'transformation obsessions' (TO). 10% of our OCD paediatric sample endorsed these obsessions. Similarities and differences were noted between OCD cases with and without TO. Result indicates TO respond to standard treatment for OCD. Screening is essential for accurate identification and treatment.